Depressive Anhedonia and Creative Self‐concepts, Behaviors, and Achievements. (19th November 2020) - Silvia, Paul J.; Eddington, Kari M.; Harper, Kelly L.; Burgin, Chris J.; Kwapil, Thomas R.
Abstract: In the large literature on creativity and mental illness, relatively few studies have explored anhedonia—impairments in anticipating, seeking, and experiencing rewards. This project explored self‐reported creativity in a sample of adults who differed in depressive anhedonia, determined via face‐to‐face structured clinical interviews. Participants completed measures of everyday creativity (engaging in common creative behaviors and hobbies), creative self‐concepts (creative self‐efficacy, creative personal identity, and self‐rated creativity in different domains), and creative achievements. Compared to the control group ( n  = 52), people in the anhedonia group ( n  = 22) had significantly higher engagement in little‐c creative activities (medium effect size). Effect sizes for self‐rated creativity and creative achievement were either small or near‐zero. Taken together, the findings suggest that anhedonia deserves more attention in future research on motivational aspects of creativity.